Evaluating Partial Series Childhood Vaccination Services in a Mobile Clinic Setting. (June 2020) - Chen, Weiwei; Misra, Sanghamitra M.; Zhou, Fangjun; Sahni, Leila C.; Boom, Julie A.; Messonnier, Mark
This study aims to evaluate the cost-benefit of vaccination services, mostly partial series administration, provided by a mobile clinic program (MCP) in Houston for children of transient and low-income families. The study included 469 patients who visited the mobile clinics on regular service days in 2 study periods in 2014 and 836 patients who attended vaccination events in the summer of 2014. The benefit of partial series vaccination was estimated based on vaccine efficacy/effectiveness data. Our conservative cost-benefit estimates show that, compared with office-based settings, every dollar spent on vaccination by the MCP would result in $0.9 societal cost averted as an incremental benefit in regular service days and $3.7 during vaccination-only events. To further improve the cost-benefit of vaccination services in the MCP, decision-makers and stakeholders may consider improving work efficiency during regular service days or hosting more vaccination events.